KASIBA SEBAGAI SALAH SATU KEBIJAKAN PEMERINTAH DALAM PENYEOIAAN PERUMAHAAN’ - Purwantiasning, Ari Widyati (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract People growth and urbanization in urban area ha ’ fmplied on increasing of housing need. The problem’ ’araises, sin’ce the,·, housing supply islnwer than housing ,need, ’ especfally’, for,’middlelow ,’income people. The government had beeniliilialed todevelO ,corehc)usespoficy and offered housing development ’subsidies, fli’roiJghKPR’ (Kredif Pemilikan Ramah) for middle low ’income peoplE;:’ Based on t ispolicy, smafland middle scale housings were ser)arcitediy built ’by both public and private developers, This situ3tionimplied 0/1 araising new problems since 1he housingdevelopmenlspreadly’ squatted"ihurban areas. It impacts on un integratedpI2n:ljng and high cost’ of infrastructure maintenance. ltis important to promote a new approach to supply housing for middle low income peopl that more appropriate to urban integrated planning, named as KAS1BA (Kaw8san Slap Bangan). This paper aims to describeKASIBA in the term of goal managemem, involved <agents, and finance method. Keywords: KAS/BA, housing development, urban integrated planning